Basho's journey : the literary prose of Matsuo Basho - Matsuo, Bashō, 1644-1694 (State University of New York Press, 2005)
"In Basho's Journey, David Landis Barnhill provides the definitive translation of Matsuo Basho's literary prose, as well as a companion piece to his previous translation, Basho's Haiku. One of the world's greatest nature writers, Basho (1644-1694) is well known for his subtle sensitivity to the natural world, and his writings have influenced contemporary American environmental writers such as Gretel Ehrlich, John Elder, and Gary Snyder. This volume concentrates on Basho's travel journal, literary diary (Saga Diary), and haibun. The premiere form of literary prose in medieval Japan, the travel journal described the uncertainty and occasional humor of traveling, appreciations of nature, and encounters with areas rich in cultural history. Haiku poetry often accompanied the prose. The literary diary also had a long history, with a format similar to the travel journal but with a focus on the place where the poet was living. Basho was the first master of haibun, short poetic prose sketches that usually included haiku." "As he did in Basho's Haiku, Barnhill arranges the work chronologically in order to show Basho's development as a writer. These accessible translations capture the spirit of the original Japanese prose, permitting the nature images to hint at the deeper meaning in the work. Barnhill's introduction presents an overview of Basho's prose and discusses the significance of nature in this literary form, while also noting Basho's significance to contemporary American literature and environmental thought."--Jacket
Keywords: Matsuo, Bashō, -- 1644-1694 -- Travel -- Japan.; Matsuo, Bash*o, -- 1644-1694 -- Voyages -- Japon.; Matsuo, Bashō, -- 1644-1694; Matsuo, Bashō -- 1644-1694; Matsuo, Bashō; Japan -- Description and travel -- Early works to 1800.; Authors, Japanese -- Edo period, 1600-1868 -- Travel.; Écrivains japonais -- 1600-1868 (Époque d'Edo) -- Voyages.; Japon -- Descriptions et voyages -- Ouvrages avant 1800.; LITERARY CRITICISM -- Asian -- General.; Travel; Japan; Haibun; Reisegedicht; Reiseliteratur; 1600 - 1868; Diary; Poetry; diaries.; poetry.; Travel writing; Diaries; Early works; Diaries.; Travel writing.; Haibun.; Poetry.; Journaux intimes.; Récits de voyages.; Poésie.